Establishment of an appropriate method for determining multiple heterocyclic amines in soy products processed with various methods. (1st May 2022) - Chiang, Chow-Feng; Liao, Po-Lin; Hsu, Kao-Chiang; Chang, Chia-Chun; Lin, Jau-Tien; Yang, Deng-Jye
Highlights: The established UPLC-MSMS condition can simultaneously determine 21 HAs in 15 min. The established QuEChERS conditions can extract HAs in tofu and soy milk effectively. This study is the first to assess HAs content and their consumption for soy products. The fried tofu samples had much higher HAs level than the boiled and roasted ones. The highest HAs level consumed from the soy products was ∼374 ng/day for Whole Group. Abstract: A method using UPLC-MS/MS and a core–shell C18 column was developed to simultaneously determine 21 heterocyclic amines (HAs) in 15 min. Appropriate QuEChERS conditions were also established to conveniently extract HAs from soy products cooked with various methods. These conditions presented good analytical performance; limit of detection, limit of quantification, recovery (%), repeatability (coefficient of variation (CV) %) and intermediate precision (CV%) were 0.008 ∼ 0.150 ng/g, 0.025 ∼ 0.500 ng/g, 62 ∼ 91%, ≤ 28% and ≤ 23% for tofu sample, and 0.003 ∼ 0.100 ng/g, 0.010 ∼ 0.350 ng/g, 64 ∼ 93%, ≤ 19% and ≤ 20% for soy milk sample, respectively. HAs contents in the samples increased with cooking temperature and time. The tofu samples cooked by frying had much higher HAs content than those cooked by boiling and roasting. Norharman and Harman mainly contributed HAs content in all samples. For the general population in Taiwan, the highest estimated level of HAs consumed from the samples is 373.67 ng/day.